2021
DOI: 10.1097/md.0000000000024561
|View full text |Cite
|
Sign up to set email alerts
|

COL5A2 as a potential clinical biomarker for gastric cancer and renal metastasis

Abstract: Background: Gastric cancer, characterized by insidious onset and multiple metastasis, is almost incurable and has poor prognosis, and also one of the leading causes of treatment failure and death in patients with gastric cancer (GC). However, the prognosis of collagen type V alpha2 chain (COL5A2) in GC and renal metastasis is unknown. Methods: Recruited 148 patients who underwent GC. The diagnosis of GC was confirmed by ultrasound imaging and pathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Recent studies associate these molecules with processes such as migration, invasion, and poor overall survival. Moreover, inhibition of the gene expression reduces cell proliferation and invasion [ 34 , 37 , 38 , 39 , 40 , 41 , 42 ]. The overexpression of biglycan (BGN) was also identified in GC and was associated with poor prognosis, while inhibition of BGN enhanced chemotherapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies associate these molecules with processes such as migration, invasion, and poor overall survival. Moreover, inhibition of the gene expression reduces cell proliferation and invasion [ 34 , 37 , 38 , 39 , 40 , 41 , 42 ]. The overexpression of biglycan (BGN) was also identified in GC and was associated with poor prognosis, while inhibition of BGN enhanced chemotherapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen type V alpha 2 chain (COL5A2) has previously been reported to be involved in various pathological processes in tumorigenesis and cancer progression, such as cancer cell survival, migration, immune microenvironment, angiogenesis and blood vessel development [ 25 , 26 ]. The expression level of COL5A2 can also effectively predict patient outcomes in multiple malignant tumors, including gastric cancer, bladder cancer and tongue squamous cell carcinoma [ 27 29 ]. EPHB2 is a member of the erythropoietin-producing hepatocellular (Eph) receptor family, which plays a critical role in various physiological and pathological functions, such as cell adhesion and migration, stemness and angiogenesis [ 30 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…EGF mediates the activation of Rab35 by DENND1A to regulate GC invasion and migration (Ye et al, 2018). A retrospective study found that COL5A2 was a potential risk factor for prognosis in GC patients (P < 0.001, HR = 18.834) (Ding et al, 2021). The above genes have been confirmed to be important participants in the development of GC, and we are also the first to find that they are important markers for GC stratification from a holistic perspective.…”
Section: Discussionmentioning
confidence: 84%